2004
DOI: 10.1002/ppp.493
|View full text |Cite
|
Sign up to set email alerts
|

Geophysical surveys designed to delineate the altitudinal limit of mountain permafrost: an example from Jotunheimen, Norway

Abstract: Three geophysical methods have been applied to delineate the altitudinal limit of permafrost at Juvvasshøe/Jotunheimen in southern Norway. By using each method in a complementary way according to its applicability, the permafrost distribution could be analysed on both large and small scales. In addition, temperature-based methods such as the BTS method (bottom temperature of snow cover) were used to validate the results. On a large scale, electromagnetic induction profiling with the EM-31 was used to detect th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
76
0
1

Year Published

2007
2007
2017
2017

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 73 publications
(77 citation statements)
references
References 23 publications
0
76
0
1
Order By: Relevance
“…Several previous studies have shown the benefits of combining more than one geophysical technique for mapping permafrost (e.g., De Pascale et al, 2008;Hauck et al, 2004;Schwamborn et al, 2002); in this study the GPR and ERT data also provided complementary information that allowed for interpretations that would not have been possible by using only one of the two data sets. Of course, combining multiple techniques for inference compounds our estimate uncertainties.…”
Section: On the Complementary Nature Of The Geophysical Techniquesmentioning
confidence: 85%
See 1 more Smart Citation
“…Several previous studies have shown the benefits of combining more than one geophysical technique for mapping permafrost (e.g., De Pascale et al, 2008;Hauck et al, 2004;Schwamborn et al, 2002); in this study the GPR and ERT data also provided complementary information that allowed for interpretations that would not have been possible by using only one of the two data sets. Of course, combining multiple techniques for inference compounds our estimate uncertainties.…”
Section: On the Complementary Nature Of The Geophysical Techniquesmentioning
confidence: 85%
“…Electrical resistivity tomography (ERT) has also been widely applied in permafrost studies (Hauck et al, 2003;Ishikawa et al, 2001;Kneisel et al, 2000), the majority of which focus on mountain permafrost. By combining two or more geophysical methods complementary information can often be acquired raising the confidence in interpretations of permafrost characteristics (De Pascale et al, 2008;Hauck et al, 2004;Schwamborn et al, 2002). For example, De Pascale et al (2008) used GPR and capacitive-coupled resistivity to map ground ice in continuous permafrost and demonstrated the added value of combining radar and electrical resistivity measurements for the quality of interpretation of the data.…”
Section: Y Sjöberg Et Al: Geophysical Mapping Of Palsa Peatland Permentioning
confidence: 99%
“…These findings have been transferred to field applications of p-wave velocity refraction seismics to various sedimentary landforms in polar environments (Bonner et al, 2009;Harris and Cook, 1986;King, 1984;Kurfurst and Hunter, 1977;Roethlisberger, 1961;Zimmerman and King, 1986) and to rock glaciers (Barsch, 1973;Hausmann et al, 2007;Ikeda, 2006;Musil et al, 2002), to bedrock (Hauck et al, 2004) and to talus slopes (Hilbich, 2010) in mountainous regions. Akimov et al (1973) note the discrepancy between seismic laboratory and field investigations.…”
Section: Introductionmentioning
confidence: 94%
“…Nevertheless, numerous studies successfully applied refraction seismic surveys in permafrost terrain (e.g. Röthlisberger, 1972;Barsch, 1973;Harris and Cook, 1986;Vonder Mühll, 1993;Musil et al, 2002;Hauck et al, 2004;Ikeda, 2006;Hausmann et al, 2007;Maurer and Hauck, 2007). Main advantages of the method, compared to ERT surveys, are e.g.…”
Section: Motivationmentioning
confidence: 99%